2001
DOI: 10.1006/nimg.2001.0840
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Substrates of Perceptual Stability during Eye Movements

Abstract: We are usually unaware of retinal image motion resulting from our own movement. For instance, during slow-tracking eye movements, the world around us remains perceptually stable despite the retinal image slip induced by the eye movement. This example of perceptual invariance is achieved by subtracting an internal reference signal, reflecting the eye movement, from the retinal motion signal. If the two cancel each other, visual structures, which do not move, will also be perceived as nonmoving. If, however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Nevertheless, the visual world seems stable during eye movements. Thier et al [146] investigated this using the Filehne illusion. They found the first effect in the VEP around 300 ms and concluded that the distinction between both types of motion is achieved upstream from area MT from which the earlier N2 arises.…”
Section: Eye Movementsmentioning
confidence: 98%
“…Nevertheless, the visual world seems stable during eye movements. Thier et al [146] investigated this using the Filehne illusion. They found the first effect in the VEP around 300 ms and concluded that the distinction between both types of motion is achieved upstream from area MT from which the earlier N2 arises.…”
Section: Eye Movementsmentioning
confidence: 98%
“…Recent neurophysiological studies in monkeys showed that MT activity was mostly correlated with target motion on the retina, whereas responses of some MST neurons were correlated with target motion on the screen, i.e., relative to the head and independent of the pursuit response (Chukoskie and Movshon 2009;Inaba et al 2007). The finding that some MST neurons veridically encode retinal image motion during pursuit indicates that neurons in higher cortical visual areas compensate for eye-movement-induced motion signals during pursuit (see also Bradley et al 1996;Dicke et al 2008;Shenoy et al 1999, Thier et al 2001.…”
Section: Effects Of Eye Movements On Motion Perceptionmentioning
confidence: 99%
“…This implies a corrective mechanism within the oculomotor networks of the brain. One model of this mechanism, based closely on the classical concepts of Efferenzkopie (“efference copy”) by von Holst and Mittelstaedt [3] and Willensanstrengung (“effort of will”) by von Helmholtz [7], postulates a cancellation process mediated at least in part by an internal reference signal [8]. This internal reference signal, generated from a CD that represents each eye movement, is a prediction of the imminent retinal image motion.…”
Section: Introductionmentioning
confidence: 99%